Textual, Moral and Psychological Voices of Translation - Taivalkoski-Shilov Kristiina (Russian Federation, 2022)
The concept of voice has engendered a growing amount of research in translation studies
in the last decades, especially regarding literary translation. Voice is typically used in studies
that investigate stylistic or structural characteristics of translated texts, intertextuality and
other forms of multivocality and ethical questions related to agency, ideology and power in
translation and interpreting. The first part of this article defines two essential concepts related
to voice in translation — voice and text — and describes the state of the art of research in this
field. The second part aims to deepen the discussion on voice in translation studies by introducing
the notion of the voice of conscience from philosophy and political science and the notion
of inner voices from psychology.